Evaluate the science books content at the primary stage in light of the national standards for science curricula in the Kingdom of Saudi Arabia - Al-Ajlan, Maha Saleh (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to evaluate the content of fourth grade science books content at the primary stage in light of the national standards for science curricula in the Kingdom of Saudi ArabiaThe study concluded the following results: Identifying the availability level of the standards the life sciences branch in the science books content for the primary stage in light of the national standards for science curricula in public education. The study used the descriptive analytical method. It was applied to science books (student) for the fourth grade in the primary stage, the number of (2) books in the Kingdom of Saudi Arabia for the academic year 1442/1443 AH, content analysis cards developed in light of national standards were used as a data collection tool and the study was applied in the second semester of the year 1442-1443 AH.The study concluded the following results:Availability level for the Life Sciences branch is “low” with an arithmetic mean (,57) out of (2), the availability level for the physical sciences branch is “Medium” with an arithmetic mean (1.2) out of (2), and the availability level for the Earth and Space Sciences branch is “low” with an arithmetic mean of (,33) out of (2). The study recommended the following:Alignment between national standards, the science textbooks content in different classroom, and the development of science books in the light of national standards.
Keywords: science; primary school; national standards; content standards; performance standards